Atuação docente no atendimento pedagógico domiciliar em casas de apoio para alunos em tratamento de saúde - Ziotti, Mariana Coimbra (2021)
Home Pedagogical Care (HPC) represents a right to educational care, which is guaranteed by law, since illness may have a transitory or permanent character. For sick children and teenagers, it is possible to carry out the HPC, which consists of pedagogical assistance that takes place in the home environment for the student who, due to a health problem, is unable to go to school. The present study had as general objective to analyze the performance of the teacher who performs the HPC in support houses for students in health treatment. The specific objectives were to: (a) Identify existing support homes in the state of São Paulo and verify which ones offer HPC; (b) Describe the organization and functioning of this type of care provided in support homes for students undergoing health treatment and (c) Analyze the pedagogical practices developed by teachers in the context of HPC in support homes for students undergoing health treatment. Two research stages were carried out. In the first, an exploratory study was carried out and the support homes for students undergoing health treatment in the state of São Paulo were mapped in order to identify which ones offered the HPC or other ways of monitoring the schooling process of these children and / or teenagers, as well as to identify if there was an expectation of offering this service, if the support home did not offer it. In this stage, the data were analyzed in thematic analysis. In the second stage of the research, a case study was performed with the teachers who worked in the HPC in this space. For this, semi-structured interviews were conducted with these professionals and observations were made of the pedagogical practices, in loco, of one of the homes to understand how the teacher performed the class, how teacher prepared the teaching environment, which pedagogical resources were used, how they record the activities, how is the moment when the teacher arrives at the support home to organize the class, among others that were recorded in a field diary. Data analysis were based on data triangulation. The results of stage one demonstrated that there are three support homes in the state of São Paulo that offer HPC and that in some institutions that do not offer this service, school-age patients attend regular school or hospital classes. The results of step two pointed out the specificities of the teaching performance in the HPC and highlighted how much this service is necessary both to maintain the link with the students' home school, and to provide the quality schooling process for the sick children and teenagers who are staying in support homes.